KEMAMPUAN MENDESKRIPSIKAN HUBUNGAN ANTAR KONSEP FISIKA SISWA SMP DALAM PEMBELAJARAN BERBASIS FREE INQUIRY DALAM UPAYA MENINGKATKAN KEMAMPUAN GENERIK SAINS - Suyana, Iyon (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2011)
In an effort to develop the generic skills of science students conducted research to reveal the ability to describe the relationship between the concept of students in learning science / physics topic in class IX Ohms Law. To know how to profile a students ability in describing the relationship between the concepts of physics on the topic of Ohms Law of Free Inquiry-based learning carried out in one class IX SMP Negeri 2 Cikalongwetan. Achieving the ability of students and percentage of students who achieve the ability to describe every aspect of the relationship between concepts is measured by observation and assessment products in the form of journal the results of the experiment. The results of this study indicate that the highest and lowest achieving students to aspects of the writing tables in the indicator unit 59% and 12% of the write indicator; create a chart on the indicator to write on both axes coordinate the writing of 78% and the indicator unit on the second coordinate axis 22%; describe relationships between concepts in the form of sentences in two variables load indicator 100% and the indicator shows the quality of the relationship between variables 35%; and describe the relationships between concepts in the form of symbols on the indicator symbol contains 87% 2 variables and indicators to formulate the relationship between symbols 13%. Prosentase students who can show the ability to create tables and graphs the results of the experiment, describing the relationship between concepts in the form of words and symbols in a row is 56%, 73%, 61%, and 50%.Keywords: description, generic science skill